Identity Construction in Young Law Offenders from a Cultural Psychological Perspective - Zambrano Constanzo, Alba; Pérez-Luco Arenas, Ricardo (Revista de Psicología, 2004)
The present article approaches the process of construction of criminal identity through a psychocultural theoretical analysis that nourishes itself from different sources of contemporary psychology and other disciplines, deriving in the claim that this process becomes determinant of the sprouting and consolidation of criminal behavior. It is argued that, in the case of an important number of young people, the infraction of law turned into a pattern of recurrent behaviour as the result of a process that has a strong relationship with disadvantageous social environments, generating insecurity, stress, hopelessness and difficulties in the satisfaction of material and psychological basic needs. These issues, among others, induce the construction of a social reality that locates certain young people off the margins of socially accepted standards. Finally, in the light of this theoretical analysis, some general strategies are set forth in order to approach this dimension of our reality.